2013
DOI: 10.1103/physreve.88.032602
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical crossover between hyperdiffusion and subdiffusion of polymer-grafted nanoparticles in a polymer matrix

Abstract: The dynamical behavior of polystyrene-grafted silica nanoparticles dispersed in an atactic polystyrene matrix was studied using x-ray photon correlation spectroscopy. The time-autocorrelation functions were subjected to fitting analyses based on continuous-time random walk models. The nanoparticles exhibited non-Brownian behavior, and as the temperature increased, the crossover from hyperdiffusion to subdiffusion occurred at 1.25T_{g}, where T_{g} is the glass transition temperature of the matrix polystyrene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 42 publications
4
34
0
Order By: Relevance
“…Similar results were obtained for slightly lower silica particle concentrations, also obeying the requirements for tracer particles. The change to hyperdiffuse dynamics is in line with recent studies on different glass formers [22][23][24] where such transitions were observed in a temperature region around 1.1T g -1.2T g . However, due to experimental restrictions, these studies only reported the transition from C to B without accessing the low-temperature region A.…”
Section: -3supporting
confidence: 91%
See 3 more Smart Citations
“…Similar results were obtained for slightly lower silica particle concentrations, also obeying the requirements for tracer particles. The change to hyperdiffuse dynamics is in line with recent studies on different glass formers [22][23][24] where such transitions were observed in a temperature region around 1.1T g -1.2T g . However, due to experimental restrictions, these studies only reported the transition from C to B without accessing the low-temperature region A.…”
Section: -3supporting
confidence: 91%
“…This transition was observed at T ≈ 1.2T g and discussed in the context of cooperative dynamics at low temperatures. Similar observations were made by Guo et al [23] and Hoshino et al [24] studying tracer particles in different polystyrene samples. However, these studies could report only results down to temperatures of 1.1T g -1.2T g and dynamical heterogeneities were not addressed.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Studies show that dispersion in a polymer matrix can be controlled by varying the ratio of the brush to matrix molecular weight (P/N). 1,[26][27][28] Hoshino et al 29 investigated the dynamics of polystyrene (PS)-grafted silica nanoparticles (110 nm) in unentangled PS melts using X-ray photon correlation spectroscopy (XPCS) and observed that nanoparticles followed sub-diffusive behavior when the annealing temperature was greater than 1.25T g , where T g is the glass transition of the PS matrix. This sub-diffusive behavior was attributed to the penetration of short matrix chains into the brush.…”
Section: Introductionmentioning
confidence: 99%